PENGARUH KUALITAS PELAYANAN DAN TINGKAT SUKU BUNGA TERHADAP KEPUASAN NASABAH DEPOSITO PADA BPR DANA CENTRAL MULIA - Hendi Suprianto; Suhardi Suhardi (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Currently, the business environment is moving very fast and dynamic in a short time resulting in increasingly fierce competition, as well as retaining loyal customers, one of which is BPR which is currently spreading rapidly, resulting in very tight and challenging competition. One of them is competition in product diversity where each BPR has different products so that it can attract the attention of customers who save or make deposits. However, the quality of service is very important for customers to keep saving in the long term. As a financial institution that relies on the interest rates offered by banks, it will affect deposit customer satisfaction so that customers feel safe and comfortable during transactions. In the banking world, many competitors influence each other, including service quality, interest rates and customer satisfaction. This study aims to determine the quality of service, interest rates affect customer satisfaction deposits at BPR Dana Central Mulia. The research design used is causality research related to a quantitative approach. The sample was determined using probability sampling as many as 105 respondents. Collecting data using a questionnaire measured by a Likert scale. The collected data were analyzed using the SPSS version 25 program. The results obtained were t count service quality 3,492, interest rate 5,996, each sig zero compared to t table 1,983 then t count > t table, for the f count test 64,449 > f table 3.09 concluded that service quality and interest rates have a significant and simultaneous effect on customer satisfaction on deposits at BPR Dana Central Mulia Batam.